A systematic review of the outcomes reported in trials of medication review in older patients: the need for a core outcome set. (18th January 2017) - Beuscart, Jean‐Baptiste; Pont, Lisa G.; Thevelin, Stefanie; Boland, Benoit; Dalleur, Olivia; Rutjes, Anne W. S.; Westbrook, Johanna I.; Spinewine, Anne
Abstract : Aim: Medication review has been advocated as one of the measures to tackle the challenge of polypharmacy in older patients, yet there is no consensus on how best to evaluate its efficacy. This study aimed to assess outcome reporting in trials of medication review in older patients. Methods: Randomized controlled trials (RCTs), prospective studies and RCT protocols involving medication review performed in patients aged 65 years or older in any setting of care were identified from: (1) a recent systematic review; (2) RCT registries of ongoing studies; (3) the Cochrane library. The type, definition, and frequency of all outcomes reported were extracted independently by two researchers. Results: Forty‐seven RCTs or prospective published studies and 32 RCT protocols were identified. A total of 327 distinct outcomes were identified in the 47 published studies. Only one fifth (21%) of the studies evaluated the impact of medication reviews on adverse events such as drug reactions or drug‐related hospital admissions. Most of the outcomes were related to medication use ( n  = 114, 35%) and healthcare use ( n  = 74, 23%). Very few outcomes were patient‐related ( n  = 24, 7%). A total of 248 distinct outcomes were identified in the 32 RCT protocols. Overall, the number of outcomes and the number and type of health domains covered by the outcomes varied largely. Conclusion: Outcome reporting from RCTs concerning medication review in older patients is heterogeneous. This review highlights the need for a standardized core outcome set for medication review in older patients, to improve outcome reporting and evidence synthesis.